2013
DOI: 10.5487/tr.2013.29.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on Acetaminophen Hepatotoxicity: The Role of Nrf2 in Hepatoprotection

Abstract: Acetaminophen (APAP) known as paracetamol is the main ingredient in Tylenol, which has analgesic and anti-pyretic properties. Inappropriate use of APAP causes major morbidity and mortality secondary to hepatic failure. Overdose of APAP depletes the hepatic glutathione (GSH) rapidly, and the metabolic intermediate leads to hepatocellular death. This article reviews the mechanisms of hepatotoxicity and provides an overview of current research studies. Pharmacokinetics including metabolism (activation and detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 52 publications
3
59
0
1
Order By: Relevance
“…NRF2 plays a critical role in the multiple steps related to the alleviation of APAP toxicity and thus is identified as a protective target resistant to liver injury (Gum and Cho, 2013). Furthermore, liver repair is a critical determinant of final outcome of toxicant-induced injury (Diehl and Chute, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 plays a critical role in the multiple steps related to the alleviation of APAP toxicity and thus is identified as a protective target resistant to liver injury (Gum and Cho, 2013). Furthermore, liver repair is a critical determinant of final outcome of toxicant-induced injury (Diehl and Chute, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because NAPQI covalent binding and APAP protein adducts have already been formed before 4 hours after APAP exposure, GSH replenishment is not a prerequisite event for NRF2 regulates the expression of a battery of cytoprotective genes encoding intracellular detoxifying enzymes and antioxidant proteins that are responsible for GSH synthesis, antioxidant defense, conjugation, transport, and excretion of the metabolites through ARE (Chan et al, 2001). NRF2 plays a critical role in the multiple steps related to alleviation of APAP toxicity and is identified as a protective target for resistance to liver injury (Gum and Cho, 2013). WZ reversed the decreased protein expression of NRF2 target genes including Gclm, Gclc, Nqo1, and Ho-1 by APAP and promoted the recovery of these proteins compared with saline or NAC treatment during APAP-induced liver injury.…”
Section: Discussionmentioning
confidence: 98%
“…Activated Nrf-2 by dissociation from Kelch-like epichlorohydrin-associated protein 1 (Keap1), translocates to the nucleus and binds to the antioxidant response element (ARE) in the promoter region and transcribes a large battery of antioxidant genes (Gum & Cho, 2013;Lee & Pan, 2013). Extensive study reports have demonstrated the fact that Nrf-2 mediated gene regulation is effectually involved in hepatoprotective activity against acetaminophen.…”
Section: Fig 4 -Dose Dependent Effect Of Moringa Oleifera (Mo) Leavementioning
confidence: 99%